Polygamy in Nasr Hamid Abu Zayd’s Perpective - Siti Robikah (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
Polygamy is still a debatable topic. It is founded on QS An- Nisa's which permits having more than one wife under fair conditions. Nasr Hamid Abu Zayd was one of the mufassir figures who attempted to revise the previous mufassir figures' beliefs or interpretations. He tries to elaborate the polygamy verse's implicit meaning using his hermeneutic method. Abu Zayd's technique is divided into two parts; importance and maghza. The significance meaning things can be determined by recalling the time. Maghza is a word that does not appear in the stanza. Hence, the underlying meaning of the text is that monogamy exists because a husband's justice is unachievable.